Association between NAFLD and liver fibrosis with nutritional risk index based on the NHANES 2017–2018 - Jieming Jian; Rui Zhang; Yuan Dong; Hongting Zheng; Xiaoyu Liao (Lipids in Health and Disease)
Abstract Background Nutrition and its associated inflammation have been acknowledged as vital factors in the etiopathogenesis of non-alcoholic fatty liver disease (NAFLD) and liver fibrosis. The nutritional risk index (NRI) has been widely recognized as a valid indicator of nutritional status in several diseases, including osteoporosis and cardiovascular disease. However, the role of NRI in NAFLD and liver fibrosis remains unclear. Methods Participants were selected from the National Health and Nutrition Examination Survey data for the 2017–2018 cycle. Association between NRI and both NAFLD and liver fibrosis was evaluated using multiple logistic regression and restricted cubic spline (RCS) analysis. Mediation analysis was employed to assess the influence of inflammation on the association between NRI and both NAFLD and liver fibrosis. Results Compared to their respective control groups, individuals with NAFLD and liver fibrosis exhibited higher NRI levels. Multiple logistic regression analyses indicated that NRI was positively associated with the odds of NAFLD and liver fibrosis across both continuous scales and quantile groups, with adjustments for relevant covariables. The RCS model demonstrated a dose-response effect between NRI and the odds of NAFLD, but not with liver fibrosis. Receiver operating characteristic (ROC) analysis revealed the area under the ROC curves of 0.798 and 0.775 for NAFLD and liver fibrosis, respectively. Mediation analysis showed that inflammation accounted for 3.139% of the effect of NRI on the odds of NAFLD, suggesting inflammation might partially mediate the impact of NRI on NAFLD. Conclusions Our findings indicate that NRI may serve as a potential associated marker for these liver diseases, underscoring the importance of nutritional status in their etiopathogenesis.